Huge uterine myomas complicated the pregnancy in 47-year old pregnant woman. Case report and review of the literature - Kowalska-Koprek, Urszula; Kuś, Ewa; Berner-Trąbska, Marlena; Nawarra, Dagmara; Kulik, Viachlaslau; Kazimierak, Wojciech (Menopause Review/Przegląd Menopauzalny, 2004)
During last decades because of changes in life conditions the fertility period is being prolonged. It is accompanied by increased rate of pregnancies in women after 45 year old. In this paper the case of pregnant woman with huge uterine myomas was described and the most important obstetrical aspects of women of this age were analyzed. It is established that pregnancy after 48 year of women life is a pregnancy of increased obstetric risk. In the cases of uterine leiomyomas occurrence, which may disorder the uterine foetus development the surgical intervention should be considered. In these cases such pregnant women should be delivered by cesarean section in term of labour, what allows for additional assessment the uterus and likely supply the range of the first surgical procedure.